(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
The paper presents the functioning regimes of a 132 kW asynchronous three-phase machine, used for the expander-generator system in a compressed air energy storage facility. The installation consists of a 110 kW twin-screw electro-compressor, which supplies pressurized air up to 16 bar into a 50 m3 storage vessel. The compressed air is afterward released from the reservoir into the expander’s inlet, spinning its shaft. When the expander’s shaft spins the electric machine over its synchronous speed, this one enters in generator mode, supplying electric power into the grid. Two power analyzers installed on the automation control cabinet monitor the generated/absorbed power and the power supplied/consumed by the system from the grid. Using the data acquired by means of PLC during commissioning tests, we plotted the power curves, differential pressure, and significant temperatures, as well as the electric machine’s speed.